2007
DOI: 10.1021/jp075986e
|View full text |Cite
|
Sign up to set email alerts
|

Signal Enhancement and Tuning of Surface Plasmon Resonance in Au Nanoparticle/Polyelectrolyte Ultrathin Films

Abstract: Investigations on optical and dielectric properties of hybrid ultrathin layer-by-layer (LbL) films of gold nanoparticles (AuNPs) and polyelectrolytes under different pH conditions resulted in surface plasmon resonance (SPR) signal enhancement under attenuated total reflection (ATR) spectroscopy conditions. Theoretical considerations on the basis of the Maxwell-Garnett theory were made to compare with experimental results. LbL films with different layer architectures were fabricated from AuNPs and two polyelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 43 publications
3
66
0
Order By: Relevance
“…Surface plasmons (SPs) are coherent oscillations of free electrons that propagate along the surface of a metal when it is in contact with a dielectric interface [8][9][10][11][12][13]. SPs of the metal surface are greatly affected by adsorption and/or desorption events that occur at a metal/dielectric interface.…”
Section: Introductionmentioning
confidence: 99%
“…Surface plasmons (SPs) are coherent oscillations of free electrons that propagate along the surface of a metal when it is in contact with a dielectric interface [8][9][10][11][12][13]. SPs of the metal surface are greatly affected by adsorption and/or desorption events that occur at a metal/dielectric interface.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that the electrons are transferred from SWNT to methyl viologen inside the film, since such small molecules can exist inside LbL films in electrolyte solution. This is reasonable because LbL films usually contain electrolytes in aqueous solution (Jiang et al, 2007;Baba et al 2002). These results indicate that the TMPyP-SWNT/SCC-SWNT LbL multilayered film should have potential for effective photocurrent generation.…”
Section: Photocurrent Properties Of Lbl Filmsmentioning
confidence: 61%
“…Upon changing the pH from 5 to 2, the distance change between the AuNPs and the gold islands also changed the extent of interparticle coupling in LSPR, which resulted in a wavelength shift of the absorption peak maximum of 50 nm, as compared with only 6 nm in the absence of the NPs. Another example of enhanced LSPR sensing was reported by Jiang et al, 55 who modulated the packing of AuNP in a multilayer fi lm of pAH and pSS prepared by LBL deposition on gold by changes in pH. Using the planar SPR mode, they showed that pH -induced changes in the packing of the AuNPs strongly affected the SPR response.…”
Section: Optical Transductionmentioning
confidence: 95%
“…26 To enhance the sensitivity, hybrid polymer coatings with AuNPs embedded in the polymer matrix are often used. 26,27,55 In addition to the change in the refractive index of the coating, the swelling/shrinking of the polymer changes the interparticle plasmon ) and nanoparticles, which generates a shift in the absorbance peak. Adapted with permission from references [17], [29], [67], [88], and [91] .…”
Section: Optical Transductionmentioning
confidence: 99%